2019
DOI: 10.1007/978-3-030-29436-6_22
|View full text |Cite
|
Sign up to set email alerts
|

Towards Bit-Width-Independent Proofs in SMT Solvers

Abstract: Many SMT solvers implement efficient SAT-based procedures for solving fixed-size bit-vector formulas. These approaches, however, cannot be used directly to reason about bit-vectors of symbolic bit-width. To address this shortcoming, we propose a translation from bit-vector formulas with parametric bit-width to formulas in a logic supported by SMT solvers that includes non-linear integer arithmetic, uninterpreted functions, and universal quantification. While this logic is undecidable, this approach can still s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…To overcome this limitation, a later paper by Niemetz et al [10] suggested a translation from bit-vector formulas with parametric bit-widths to the theory of (non-linear) integer arithmetic with uninterpreted functions. Thanks to this translation, the authors were able to verify, with the aid of SMT solvers for the theory of integer arithmetic with uninterpreted functions, the correctness of 110 out of 160 invertibility equivalences.…”
Section: Invertibility Conditions and Their Verificationmentioning
confidence: 99%
See 4 more Smart Citations
“…To overcome this limitation, a later paper by Niemetz et al [10] suggested a translation from bit-vector formulas with parametric bit-widths to the theory of (non-linear) integer arithmetic with uninterpreted functions. Thanks to this translation, the authors were able to verify, with the aid of SMT solvers for the theory of integer arithmetic with uninterpreted functions, the correctness of 110 out of 160 invertibility equivalences.…”
Section: Invertibility Conditions and Their Verificationmentioning
confidence: 99%
“…In the rest of this paper we describe our initial efforts and future plans for proving the invertibility equivalences, starting with those that were not proved in [10].…”
Section: Invertibility Conditions and Their Verificationmentioning
confidence: 99%
See 3 more Smart Citations